Students' Social, Emotional, and Creative Abilities Using School Learning Mobilization Community (SLMC) Project - Rulyansah, Afib (International Journal of Elementary Education, 2022)
Several researchers have warned in recent years about the need to teach children to think critically, creatively, cultivate emotional and social skills. Educators have an important regulation in the main emotions of their students. The primary objective was to improve learning by encouraging the acquisition of foundational awareness within the structured curriculum and by stimulating the development of practical and analytical reasoning abilities, resilience and commitment, in addition to technological, emotional, social, and creative skills. This study uses a descriptive-exploratory study which is part of a qualitative approach. Seven elementary school teachers were involved in this research as research subjects. Semi-structured interviews were used in data collection. Content analysis was chosen as the analytical method because it is very suitable to handle qualitative information. The results show a significant increase in the professional and personal growth of educators. Behavior, student-teacher relationships, and the overall atmosphere in the classroom reportedly improved, according to the teachers. They emphasized the need to include learning in emotional development in teacher preparation programs. It is clear that teachers need to receive more training as well as socio-emotional education in the educational process. It can be claimed that influencing the instructor has a domino effect on pupils, while also improving the learning and teaching process.